2022
DOI: 10.24815/siele.v9i2.23440
|View full text |Cite
|
Sign up to set email alerts
|

Fostering students’ Multimodal Communicative Competence through genre-based multimodal text analysis

Abstract: The multiplicity of semiotic resources employed in communication, the rapid advancement of information, communication, and technology (ICT), and burgeoning interdisciplinary research into multimodality have led to a paradigmatic shift from a mono-modal to the multimodal perspective of communication. Conversely, actualising multimodal concepts in teaching and learning practises remains underexplored, notably in developing the students’ multimodal communicative competence (MCC). For this reason, this study endea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Multimodality refers to the use of communication modes in which diverse semiotic sources (such as language, visual images, movements, spaces, movements, audio, and audio-visual modes) are contextualized to enrich the meaning of Indonesia's local culture. Multimodal tools can analyze cultural values, political movements, educational discourses, and represented ideologies [32]. As parameters, van Leeuwen suggested modeling multimodal semiotic sources, color, typography, volume, sound quality, and tone) which is conducted in three stages.…”
Section: Discourse Analysismentioning
confidence: 99%
“…Multimodality refers to the use of communication modes in which diverse semiotic sources (such as language, visual images, movements, spaces, movements, audio, and audio-visual modes) are contextualized to enrich the meaning of Indonesia's local culture. Multimodal tools can analyze cultural values, political movements, educational discourses, and represented ideologies [32]. As parameters, van Leeuwen suggested modeling multimodal semiotic sources, color, typography, volume, sound quality, and tone) which is conducted in three stages.…”
Section: Discourse Analysismentioning
confidence: 99%
“…Using a multimodal medium such as film in the classroom has also been shown to be beneficial, as Steckmest (2021) discovered in her research that it is interesting, enjoyable, and engaging throughout the teaching and learning process. Next, Abdullah et al (2022) revealed that their learners gained more knowledge in multimodality in language learning and engaged in more theoretical and practical activities in the classroom. These examples clearly demonstrate that learning through multimodal mediums rather than just texts is beneficial to learners.…”
Section: Multimodal Mediummentioning
confidence: 99%